SOFTWARE FOR CALCULATING NODE CONNECTIONS MONOLITHIC REINFORCED CONCRETE BEAMLESS NON-CAPITAL OVERLAP WITH THE COMPOSITE REINFORCED CONCRETE COLUMN (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article touches upon the calculation procedure issue of connection nodes betweenbeamless non-capital monolithic concrete slab and reinforced concrete column to providebearing capacity in junctions between the slab and the column during design using softwareThe article deals with general calculation principles of connection nodes betweenbeamless non-capital monolithic concrete slab and reinforced concrete column. On the basisof the algorithm to automate the calculation computer program was created in theprogramming language of Visual Basic for Applications (VBA). The language used fordeveloping applications designed to manipulate databases and to customize the user interface.VBA a structured high-level programming language. In the language of VBA implemented thegeneral principles of object-oriented programming.Keywords: computer technologies, beamless monolithic slab, composite reinforcedconcrete, shear, algorithm, software.